2020
DOI: 10.3390/agronomy10111721
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Segmentation and Classification with a Complicated Background Using Deep Learning

Abstract: The segmentation and classification of leaves in plant images are a great challenge, especially when several leaves are overlapping in images with a complicated background. In this paper, the segmentation and classification of leaf images with a complicated background using deep learning are studied. First, more than 2500 leaf images with a complicated background are collected and artificially labeled with target pixels and background pixels. Two-thousand of them are fed into a Mask Region-based Convolutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…For instance, Ganesh et al [50] and Jia et al [51] developed harvesting detectors based on the Mask-RCNN for robotic detections of apple and orange in orchards with precision of 0.895 to 0.975. Yang et al [52] revealed the potential of Mask-RCNN for the identification of leaves in plant images for rapid phenotype analysis, yielding the average accuracy value up to 91.5%. Tian et al [53] illustrated that Mask-RCNN performed best compared to other models including CNN and SVM in automatic segmentation of apple flowers of different growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ganesh et al [50] and Jia et al [51] developed harvesting detectors based on the Mask-RCNN for robotic detections of apple and orange in orchards with precision of 0.895 to 0.975. Yang et al [52] revealed the potential of Mask-RCNN for the identification of leaves in plant images for rapid phenotype analysis, yielding the average accuracy value up to 91.5%. Tian et al [53] illustrated that Mask-RCNN performed best compared to other models including CNN and SVM in automatic segmentation of apple flowers of different growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convolutional neural networks were developed to identify plant diseases and to predict the macronutrient deficiencies during the flowering and fruit development stage [102]. The visual geometry group (VGG) CNN architecture identified plant diseases with the leaf images of the plants and communicated the results to farmers through smart phones [103,104]. The endemic fungal infection diagnosis in the winter wheat [89] was validated and trained with Imagenet datasets and implemented with an adaptive deep CNN.…”
Section: Deep Architectures In Smart Farmingmentioning
confidence: 99%
“…Automated ROI extraction is normally based on image segmentation, but no single technique exists for ideal segmentation. [27] While on the other hand, manual and semi-automated techniques are based on expert opinion. It shows that human-based extraction has its limitations.…”
Section: Range Oriented Pixel-based Segmentation (Rops) Algorithmmentioning
confidence: 99%